DNA repair gene polymorphisms and clinical outcome of patients with primary small cell carcinoma of the esophagus - Zhou, Qiang (Tumour Biol, 2014)
Polymorphisms in DNA repair genes impact on the synthesis of DNA repair proteins that are crucial to the repair of DNA damages induced by chemotherapy and radiotherapy. We retrospectively examined whether there was an association between the selected six single nucleotide polymorphisms (SNPs) of five DNA repair genes (PARP1-Val762Ala, XRCC1-Arg194Trp, XRCC1-Arg399Gln, XPC-Lys939Gln, BRCA1-Lys1183Arg, and BRCA2-Asn372His) and the clinical outcome of patients with primary small cell carcinoma of esophagus (SCCE), and it showed that the median progression-free survival (PFS) and the overall survival (OS) were 11.8 versus 9.7 months (P = 0.041) and 17.4 versus 14.8 months (P = 0.032) for patients carrying the variant allele (T/C + C/C) and the wild-type allele (T/T) of PARP1-Val762Ala polymorphism, respectively. However, no statistical significance was observed in the other five polymorphic loci (P > 0.05). When these six SNPs were combined, however, patients with at least three variant genotypes had significantly longer PFS and OS compared with those carrying less than three variant genotypes (P = 0.009 and P = 0.007, respectively). The presence of at least three polymorphic variants in certain DNA repair genes may impact on patient survival and could be a potential genomic predictor of clinical response to DNA-damaging treatment in SCCE patients. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13277-014-2718-y) contains supplementary material, which is available to authorized users.